The Differences of Anagrams and Un-jumble in Learning English Vocabulary for Junior High School - Novianty, Melisa - (Enrich: Jurnal Pendidikan, Bahasa, Sastra dan Linguistik, 2022)
This research aimed to introduce the students through differentiate how to use Anagrams and how to use Un-jumble in vocabulary. This research used a descriptive method. The total sample was 17 students in Junior High School Number 18 Palembang in academic year 2021/2022, South Sumatera. The writer gave 10 questions of questionnaire to know about the results of their activities in learning process, especially, in writing English. The results showed that there were 47.05% students often like English, 47.05% students sometimes like English, and 5.8% students seldom like English. Therefore, this two items were very useful for them to increase knowledge and develop the way or concept to research. Besides at least, the students can use Anagrams and Un-jumble not only for English lesson, but also for another subjects